1999
DOI: 10.1021/ja9923181
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Electronic Properties of Fluorinated and Chlorinated Polyacetylene

Abstract: Using a density-functional method we have calculated the electronic and structural properties of infinite and periodic (CF) x , (CCl) x , and (CFCCl) x chains. Only for the (CF) x and (CCl) x trans isomers without a C−C bond-length alternation we have optimized the structure completely and subsequently explored whether the total energy for these isomers could be lowered upon a such alternation. Finally, we studied the electronic properties of different cis isomers with fixed structures as well as of trans a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…A at the same level of theory. These results seem to rationalize the very large LDA BLA of 0.061Å reported by Springborg [115], that was obtained in a calculation with 11 k points. Clearly, the latter result [115] is far from converged.…”
Section: Polyacetylene -Pasupporting
confidence: 85%
See 2 more Smart Citations
“…A at the same level of theory. These results seem to rationalize the very large LDA BLA of 0.061Å reported by Springborg [115], that was obtained in a calculation with 11 k points. Clearly, the latter result [115] is far from converged.…”
Section: Polyacetylene -Pasupporting
confidence: 85%
“…These results seem to rationalize the very large LDA BLA of 0.061Å reported by Springborg [115], that was obtained in a calculation with 11 k points. Clearly, the latter result [115] is far from converged. According to our estimates, in order to obtain a converged BLA value, one ought to use about 200-400 k points, which is in accord with the conclusions of Ref.…”
Section: Polyacetylene -Pasupporting
confidence: 85%
See 1 more Smart Citation
“…It has been shown that the electronic properties of polyacetylene and polyacenes alter when the hydrogen atoms are replaced with other elements or ligands. [17][18][19][20][21][22] In this regard, Aoki et al have reported experimental observations on the polymerization of cyanoacetylene molecules (HC 3 N) at pressures above 1.5 GPa into a polyacetylene-like chain, in which every second hydrogen atom has been replaced with a cyano group (CN), 23 called polyacrylonitrile. By using first-principles calculations, Springborg studied the electronic structure of polyacrylonytrile (PA) and compared its stability with a polymer with the same composition, consisting of fused pyridine rings (FPR's), similar to polyacene structure.…”
Section: Introductionmentioning
confidence: 99%
“…1B) in part because it would be more airstable than PA (9). Their computational investigations on polydifluoroacetylene and polyfluoroacetylene, as well as later reports by others (10)(11)(12), predicted that such fluorinated polyacetylene (F-PA) derivatives would have modified optical properties, improved solid-state packing, and be amenable to n-type doping for improved conductivity. Fukui and Shirakawa proposed a synthesis of polydifluoroacetylene 2 from the polymerization of pyrophoric and highly explosive mono-or difluoroacetylene gas (13).…”
mentioning
confidence: 97%